Manuels de français langue étrangère et pratiques des enseignants - Margaret Bento (Recherches en didactique des langues et des cultures)
This paper reports on an analysis of interviews carried out with novice and experienced teachers of French as a foreign language about their use of text books. We will seek to identify institutional factors (constraints related to work places, programs and knowledge-producing institutions), social factors (constraints related to learners, colleagues, programs and work places) and personal factors (perceptions of French as a foreign language, of teaching and learning methodologies and of learners) that influence this use.